Upaya Pemanfaatan Rekaman Suara Burung dan Analisis Spektrogram untuk Menyusun Metode Klasifikasi Berdasarkan Suara (Sonotaksonomi) - Marwan Irwandi; A. Hadi Mahmud; Abdulah Abdulah (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
This research explores possibility to classify bird species based on it sound.  Sound data (time-domain) plotting and its spectrum (frequency domain) are used to identify five kind of bird consist of Loriculus galgulus, Chloropsis sonnerati, Pycnonotus melanicterus, Lanius schach, and Sturnus contra.  There are indications that exist of equality sound parameter from the samples such as number of element, number of peak spectrum, dominant frequency and maximum frequency. This result open the possibility to develop method of bird species classification based on bird sound (sono-taxonomy).